Character Education in the Digital Age: Strategies for Teaching Moral and Ethical Values to a Generation that Grows Up with Technology - Mariana Ditboya Hukubun; Wakhudin Wakhudin; Rachma Putri Kasimbara (Journal of Pedagogi, 2024)
This research aims to investigate the effectiveness of strategies for teaching moral and ethical values to a generation that has grown up with technology in the digital era. This research uses the literature study method to examine character education in the digital era, with a particular focus on strategies for teaching moral and ethical values to a generation that has grown up with technology. The results of this study show that character education that is well integrated in the school curriculum can help children develop a deep understanding of moral values, such as integrity, empathy, and responsibility, which are needed in digital life. The use of technology as an educational tool has also proven effective in delivering moral messages in a way that is engaging and relevant to the digital generation. Educational apps, interactive games and multimedia content have helped strengthen students' understanding of the importance of acting ethically and responsibly in online interactions. In addition, the development of good digital literacy, which includes an understanding of data privacy, online safety, communication ethics and the ability to manage information encountered on the internet, is also an important factor in character education in the digital era. The implication of this study is the need for a holistic approach in integrating character education with digital literacy in the education curriculum. This will not only help protect children from the negative impact of technology, but also equip them with the necessary skills to face and overcome moral and ethical challenges in online life.